SINTESIS DAN KARAKTER SENYAWA KOMPLEKS Cu(II)-EDTA DAN Cu(II)- C6H8N2O2S - Nurvika, Dian (Chem Info Journal, 2013)
Has done research about the synthesis and characterization of complex compounds of Cu(II)-EDTA and Cu(II)-C6H8N2O2S. This research was conducted to obtain complex compounds Cu(II)-EDTA and Cu(II)-C6H8N2O2S and knowing the character of the complex compounds through analysis of UV-Vis, AAS and FTIR. Synthesis of Cu(II)-EDTA is done by mixing CuSO4.5H2O and EDTA ligand in aquades, and then performed with refluks and magnetic stirrer, filtered, washed and dried in a desicator. Synthesis of complexes Cu(II)-C6H8N2O2S done by mixing CuSO4.5H2O that has been reconstituted in methanol with C6H8N2O2S that has been reconstituted and magnetic stirrer. The results is obtained precipitated Cu(II)-EDTA is blue and Cu(II)- C6H8N2O2S is tawny. UV-Vis analysis results of Cu(II)-8-EDTA have a maximum wavelength at 741 nm, while maximum wavelength of Cu(II)-8 C6H8N2O2S at 813,5 nm. FTIR analysis results indicate the presence of N atom and O atom in EDTA ligand and the presence of N atom in Sulfanilamide (C6H8N2O2S 0. The stability constants of Cu(II)-EDTA of 8.09 x 102 while the Cu(II)- C6H8N2O2S of 1.9596 x 103.